Iowa RBA, August 16-20, 1999 - Fuller, James Let al; Iowa Ornithologists' Unionet al (1999)
Six emails of Iowa RBA updates for August 16 and 18-20, 1999. Highlights of the updates include sightings of a Red-necked Phalarope, a Laughing Gull, and an Arctic Tern. Epson - sheet feed/flatbed